Mapping Early Reading Difficulties: A Diagnostic Study of Second-Grade Students at MI Muhammadiyah Buntu Barana - Aida Rais, Fitri; Ismail, Ismail; Danindra, Fuad (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Beginning reading skills are a fundamental foundation for early literacy development. This study aimed to describe the forms of beginning reading difficulties experienced by second-grade students at MI Muhammadiyah Buntu Barana, identify the contributing factors, and formulate the implications of diagnostic analysis for improving reading instruction. This study employed a qualitative approach with a descriptive-diagnostic design. The subjects were second-grade students who experienced beginning reading difficulties, while the informants were the classroom teacher and the school principal. Data were collected through observation, beginning reading tests, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings showed that 8 out of 12 students, or 66.7%, experienced beginning reading difficulties. These difficulties included recognizing letters, distinguishing visually similar letters, associating letters with sounds, reading syllables, reading simple words, reading fluently, and comprehending simple texts. The contributing factors originated from internal and external aspects. The diagnostic analysis provides a basis for teachers to design more adaptive reading instruction through phonics-based approaches, visual media, gradual reading exercises, guided reading, and individualized support.